Bamboo as reinforcement in structural concrete. (2021) - Kumar, Purushottam; Gautam, Phalguni; Kaur, Simardeep; Chaudhary, Mohit; Afreen, Anam; Mehta, Tanuja
Abstract: Reinforcing steel used in reinforced concrete all over the world is very expansive that leads to the proposal of using bamboo as a reinforcement in concrete in terms of culms or strips. Due to the high cost of steel, the need for a more sustainable and effective alternative that will be relatively cheaper becomes an important issue in the construction industry. Many pieces of research are going on for the productivity and usage of bamboo as a reinforcement material. This review paper addresses the concept of bamboo-reinforced concrete and assesses the mechanical and structural performances of bamboo as an alternative to steel. Various researchers conclude that the mechanical properties of bamboo are quite extraordinary. The tests regarding the compressive, tensile, and flexural strength of the bamboo show surprisingly comparable results to the alternative steel that makes it a useful and important asset to study which might revolutionize the construction industry.